Comparative Analysis of Local and Non-Local Tourists: Assessing the Influence of Destination Image and Social Media Promotion on Visit Intention. - Surianto Surianto; Gerson Ralph Manuel Kho; Zera Edenzwo Subandi; Francis Timothy Ongkohalim (Universitas Syiah Kuala, 2025)
This study investigates the influence of destination image and social media promotion on tourists visit intention to Soedirman Street, Bandung. Using a quantitative approach, data were collected through an online survey administered to 200 respondents, comprising 100 local residents from Bandung and 100 visitors from outside the city. Employing comparative analysis, this research examines how these variables affect visit intention differently between local and non-local tourists. The results reveal that destination image significantly impacts visit intention across both groups, with a stronger effect observed among local residents. Social media promotion significantly influences non-local tourists visit intention but shows no significant effect on locals. These findings suggest that tailored marketing strategies are necessary: social media campaigns should primarily target non-local visitors, while efforts to enhance destination image and community engagement are essential to encourage local visitation. The study contributes valuable insights into urban tourism behaviour and supports sustainable tourism development in culturally diverse settings.